Analisis Hak Atas Tanah Dalam Perspektif Hadist Dan Hukum Agraria Nasional - Tierra Kresna; Tajul Arifin (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Land is something that is very important for human life. From the land humans come from, on the land humans live and into the land humans will return. Ownership, control, use and utilization of land need to be regulated in such a way in national agrarian law. In particular, land rights also need to be regulated in the agrarian law. In this context, the teachings and laws in Islam as the largest religion in Indonesia also influence the conception and policies regarding land rights. In this case, the teachings contained in the verses of the Quran and the hadith of the Prophet Muhammad SAW as a source of Islamic law become the theological and philosophical basis of the substance of land rights regulated in the constitution and other laws and regulations in Indonesia.